Development of Standard Operating Procedures in Creative Department Implemented by Selected Shopping Malls in Kuching, Sarawak - Chong, Yee Yang (Universiti Malaysia Sarawak (UNIMAS), 2018)
The aim of this thesis is to identify and produce a Standard Operating Procedures (SOP) for the Creative Department in shopping malls in Kuching Sarawak. The goals of the study were to identify SOP that are related or used in current practice from art organization and develop a usable SOP. Qualitative and quantitative or mix method is used in this study. Data were collected from guided interview from respective informants working in shopping malls management to gain information and SOP based on the Remington Creative Department SOP. All information will contribute to building up the new SOP. Quantitative data were gained by sending the questionnaire to the shopping malls art department and related department that contribute to producing artwork and event. Quantitative method is used to justify the SOP produced in this study. Data analysis is used to understand the respondents’ feedback and gain empirical data. The outcome of this study is useful for the students and working personnel in the art organization to understand the ways of building up a SOP in art related field. Furthermore, the information in this study can be used as academic information for the students to do future research on the topics related to Creative Department SOP in shopping malls.